Alasdair MacIntyre on the division of goods and “the corrupting power of institutions” - Burns, Tony (Frontiers in Sociology, 2022)
This paper examines the distinction between “internal goods” and “external goods” and its significance for the political thought of Alasdair MacIntyre, focusing especially on its relevance for our understanding of MacIntyre's views regarding the relationship which exists between “practices” and social “institutions. ” The paper explores the origins of this distinction in the writings of Plato and Aristotle, both of whom (like MacIntyre) associate the notion of external goods with such things as wealth, status and power. Plato argues that these things are not really “goods” at all, but rather “bads,” or things which ought to be avoided. Aristotle, on the other hand, takes issue with that view, arguing that the pursuit of such things is acceptable, morally speaking, provided it is in moderation and not to excess. The paper argues that what MacIntyre says about external goods and “the corrupting power of institutions” in After Virtue is ambivalent. For this reason, his views are open to different possible interpretations. Most commentators have read and understood him as a follower of Aristotle. There is however a strain of Platonism at times in the critical remarks which he makes about social institutions and those who manage them.